How constitutional rights matter - Chilton, Adam S.; Versteeg, Mila 1983- (Oxford University Press, 2020)
This Book explores whether constitutionalizing rights improves respect for those rights in practice. Drawing on global statistical analyses, survey experiments in Turkey and the U.S, and case studies in Colombia, Myanmar, Poland, Russia, and Tunisia, the book advances three claims. First, enshrining rights in constitutions does not automatically ensure that those rights will be respected. For rights to matter, rights violations need to be politically costly, which is the case when citizens punish the government for rights violations. Doing so, however, is often difficult to accomplish for unconnected groups of citizens. Second, some rights are easier to enforce than others. Specifically, some rights come with natural constituencies that can mobilize for their enforcement. This is the case for rights that are practiced by and within organizations, or "organizational rights," such as the rights to religious freedom, unionize, and form political parties. Because religious groups, trade unions and parties are highly organized, they are well-equipped to use the constitution to resist rights violations. As a result, these rights are systematically associated with better practices. By contrast, rights that are practiced on an individual basis, such as free speech or the prohibition of torture, often lack natural constituencies to enforce them, which makes it easier for governments to violate these rights. Third, even highly organized groups armed with the constitution may not be able to stop governments dedicated to rights-repression. When constitutional rights are enforced by dedicated organizations, they are thus best understood as speed bumps that slow down attempts at repression"--